PENGARUH PENGGUNAAN MODEL PEMBELAJARAN PROBLEM BASED LEARNING (PBL) BERBANTUAN MEDIA CHITCHOP DALAM KETERAMPILAN MENULIS TEKS BIOGRAFI SISWA KELAS X SMK PGRI 2 KARAWANG - Prameswari, Sheffila Putri; Triyadi, Slamet; Mujtaba, Sahlan (Silampari Bisa: Jurnal Penelitian Pendidikan Bahasa Indonesia, Daerah, dan Asing, 2024)
This research aims to determine the significant differences in the results of students' biographical text writing skills who use the Problem Based Learning (PBL) learning model assisted by ChitChop media in class X TKJ 1 students and students who use the conventional learning model (lecture) in class X TKJ 2 SMK. PGRI 2 Karawang Academic Year 2023/2024. This type of research is quasi-experimental research. The design of this research is non-equivalent post-test only control group design. The population of this study was all class X students at SMK PGRI 2 Karawang, totaling 286 students. The samples for this research were class X TKJ 1, totaling 34 people and class X TKJ 2 students, totaling 34 people. The data collection method is carried out using a test method, namely with a test instrument (description). The data obtained were analyzed using descriptive statistical analysis techniques and inferential statistical analysis techniques, namely the t-test. The results of this research show that there is a significant difference in the results of the writing skills of students who use the Problem Based Learning (PBL) learning model assisted by ChitChop media and students who use the conventional learning model (lecture). Based on the overall results of the students' answers, it can be seen that the increase that occurred in the control class of students' scores between the pre-test and post-test increased from an average score of 49.12 when the pre-test increased to 64.26, and in the experimental class there was an increase. from an average score of 64.41 during the pre-test to 78.53 during the post-test. So there is a significant difference in the results of the writing skills of students who were taught the Problem Based Learning (PBL) learning model assisted by ChitChop media and students who used the conventional learning model (lecture) in class X of SMK PGRI 2 Karawang for the 2023/2024 academic year. Keywords: Problem Based Learning (PBL), ChitChop Media, Biographical Text, Writing Skills.